Carbon coating method of lithium-rich lithium ferrite, obtained material and lithium ion battery

By deposition of carbon cladding on the surface of lithium-rich lithium ferrate material by physical vapor deposition, the problems of difficulty in processing, poor air stability and low conductivity are solved, and higher energy density and storage stability of lithium batteries are achieved.

CN119252919APending Publication Date: 2025-01-03HAIKE GRP RES INST OF INNOVATION & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411358108.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In the prior art, lithium-rich lithium ferrate materials have difficulty in processing, poor air stability and low electrical conductivity, resulting in limited application in lithium-ion batteries.

Method used

A dense and uniform carbon coating layer was deposited on the surface of lithium-rich lithium ferrate materials by physical vapor deposition. A 99.99% purity graphite target was used by magnetron sputtering at low temperature to avoid carbon reduction reactions and ensure material purity and coating uniformity. .

Benefits of technology

It improves the air stability and conductivity of the material, effectively supplements the active lithium loss during the first charging and discharging of lithium batteries, and improves the energy density and storage stability of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252919A_ABST
    Figure CN119252919A_ABST
Patent Text Reader

Abstract

The invention provides a carbon coating method of lithium-rich lithium ferrite, an obtained material and a lithium ion battery, and belongs to the technical field of lithium ion battery materials. According to the method, a physical vapor deposition method is adopted for carrying out carbon film deposition treatment on lithium ferrite particles which circularly flow in a physical vapor deposition coating device; and after deposition is completed, turning off a device power supply, and cooling to room temperature to obtain the carbon-coated lithium ferrite material. The obtained carbon-coated lithium ferrite material can effectively make up for active lithium lost in the first charging and discharging process of a lithium battery, the energy density of the lithium battery is improved, and the carbon-coated lithium ferrite material has good storage stability and conductivity in air.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion battery materials, and in particular relates to a carbon coating method for lithium-rich lithium ferrite, the obtained material and a lithium ion battery. Background Art

[0002] In the lithium-ion battery system, all active lithium comes from the positive electrode material. When the lithium-ion battery is charged and discharged for the first time, the negative electrode surface usually consumes a part of the active lithium, accompanied by the formation of the solid electrolyte membrane SEI membrane. The formation of the SEI membrane is an irreversible process. The Li used to form the SEI + During the discharge process, it can no longer be embedded in the positive electrode material, resulting in a loss of battery capacity.

[0003] In the existing technologies for solving the above problems, the method of achieving lithium replenishment is mostly to add active lithium or lithium replenishment additives to the positive and negative electrodes of lithium-ion batteries. However, negative electrode lithium replenishment usually uses lithium metal, which is a very active metal that is very easy to react in the air and has poor safety. Relatively speaking, positive electrode lithium replenishment is safer and easier to industrialize. It does not require changes to the existing equipment and processes of the factory, and is a very promising lithium replenishment technology. However, the high-lithium positive electrode materials required for positive electrode lithium replenishment still need further research, that is, the core of positive electrode lithium replenishment technology is to find a positive electrode material with a high lithium content, which can release lithium to the maximum extent under the charge and discharge conditions of existing batteries, and is low-cost, simple to prepare, and easy to use.

[0004] Lithium-rich iron oxide is a lithium-rich material with a very high specific capacity (theoretical specific capacity 867 mAh / g). The initial charge and discharge efficiency of this material is very low. It can maximize the removal of lithium and replenish the active lithium permanently consumed in the negative electrode. Therefore, lithium-rich iron oxide has great application potential in the field of lithium replenishment of lithium-ion batteries. However, the currently prepared lithium-rich iron oxide has extremely poor air stability and low conductivity.

[0005] In order to solve the above-mentioned problems of lithium-rich lithium ferrite materials, there have been many studies on coating and modification of lithium-rich lithium ferrite materials in recent years, among which carbon coating is the most widely used. The first carbon coating method is to directly mix the lithium-rich lithium ferrite material with the carbon material for carbon coating. The advantage of this method is that the coating process is simple, but the disadvantage is also obvious, and it is easy to be unevenly coated. The second carbon coating method is to mix the iron source, lithium source and carbon source for sintering, or first sinter to synthesize lithium-rich lithium ferrite, and then mix with the carbon source for sintering to achieve material carbon coating. The disadvantage of this method is that the material may undergo carbon reduction during the high-temperature sintering process, affecting the purity. Another disadvantage is that the coating uniformity cannot be effectively guaranteed. The third carbon coating method is chemical vapor deposition carbon coating. First, lithium ferrite is synthesized with a lithium source and an iron source, and then methane / acetylene is used as a gas source CVD method to carbonize the surface of lithium ferrite. The disadvantage of this method is that the CVD carbon plating temperature is high, the energy consumption is large, and carbon reduction side reactions are prone to occur, affecting the purity of the material. Therefore, there is currently no mature method that can effectively solve technical problems such as the difficulty in processing, poor air stability, and poor conductivity of lithium-rich lithium iron oxide. Summary of the invention

[0006] The present invention provides a carbon coating method for lithium-rich lithium ferrite, the obtained material and a lithium-ion battery. The method can be used to deposit a dense and uniform carbon coating layer on the surface of the lithium-rich lithium ferrite material using a physical vapor deposition method at low temperature, thereby solving technical problems such as difficult processing, poor air stability and poor conductivity.

[0007] In order to achieve the above object, the present invention provides a carbon coating method for lithium-rich lithium ferrite, comprising the following steps:

[0008] A physical vapor deposition method is used to perform carbon film deposition on circulating lithium ferrite particles placed in a physical vapor deposition coating device;

[0009] After the deposition is completed, the device power is turned off and cooled to room temperature to obtain a carbon-coated lithium ferrite material.

[0010] Preferably, the circulation flow rate of the lithium ferrite particles in the coating device is 0.1-100 g / s. After the circulation flow is stabilized, argon gas is introduced into the coating device.

[0011] Preferably, the physical vapor deposition method is a magnetron sputtering method, the carbon source used is a graphite target with a purity of 99.99%, and the particle size D50 of the lithium ferrite particles is 2-30 μm.

[0012] Preferably, the carbon film deposition process is specifically as follows:

[0013] Turn on the vacuum system and wait until the vacuum reaches 9×10 -3Pa, preheat for 60 min, introduce argon and maintain the equipment pressure at 0.4 Pa, set the temperature to 200 ° C, the current to 3 A, the voltage to 400 V, and start carbon film deposition.

[0014] Preferably, the temperature of carbon film deposition is 100-400°C and the time is 1-180 min. It is understandable that physical vapor deposition coating below 400°C can effectively avoid carbon reduction reaction between lithium ferrite material and carbon during the coating process, ensure the high purity of the material, and further ensure a good lithium supplementation effect of the material.

[0015] Preferably, the thickness of the coating layer of the obtained carbon-coated lithium ferrite material is 30-900 nm.

[0016] Preferably, after the obtained carbon-coated lithium ferrite material is exposed to air humidity of 20% for 24 hours, its charge specific capacity is still maintained above 650 mAh / g.

[0017] The present invention also provides a carbon-coated lithium ferrite material, which is prepared by the carbon coating method described in any one of the above technical solutions.

[0018] The present invention also provides a lithium ion battery, which is prepared by using the carbon-coated lithium ferrite material described in the above technical solution.

[0019] Preferably, the lithium-ion battery comprises a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode is a lithium sheet, the positive electrode comprises a current collector and an electrode active layer bonded to the surface of the current collector, and the positive electrode active material in the electrode active layer is a carbon-coated lithium ferrite-rich material.

[0020] Compared with the prior art, the advantages and positive effects of the present invention are:

[0021] 1. The present invention forms a carbon film with uniform coating and dense structure on the surface of lithium ferrite by physical vapor deposition. On the one hand, physical vapor deposition is used for carbon coating, and the temperature of the carbonization coating process is relatively low (≤400°C), which avoids the carbon reduction reaction of the lithium ferrite material at high temperature and ensures its high purity; on the other hand, the uniform carbon layer on the surface of lithium ferrite can isolate the external environment, avoid contact between lithium ferrite and water or carbon dioxide in the air, and improve the air stability of the lithium ferrite material; finally, the electrical conductivity of lithium ferrite is relatively low, and the electrical conductivity of the material is greatly improved after carbon coating.

[0022] 2. The carbon-coated lithium ferrite material prepared by the method of the present invention can effectively make up for the active lithium lost during the initial charge and discharge process of the lithium battery, improve the energy density of the lithium battery, and has good storage stability and conductivity in the air. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1Schematic diagram of a coating device used when coating lithium titanate particles by physical vapor deposition. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Example 1

[0026] This embodiment provides a method for preparing carbon-coated lithium ferrite by physical vapor deposition, and the specific steps are as follows: Figure 1 As shown:

[0027] Placing lithium ferrite LFO particles (D50 of 2-30 μm) on a rotating sample table in a physical vapor deposition coating device, and allowing the lithium ferrite to circulate in the coating device, and after the circulation flow rate reaches 0.1-100 g / s to achieve stable circulation flow, introducing argon gas into the coating device;

[0028] The lithium titanate particles circulating in the device were coated by physical vapor deposition (magnetron sputtering, with a graphite target with a purity of 99.99%). The vacuum system was turned on and the vacuum was pumped to 9×10 -3 Pa, preheat for 60 min, introduce argon and maintain the equipment pressure at 0.4 Pa, set the temperature to 200 ° C, the current to 3 A, the voltage to 400 V, and start depositing the carbon film;

[0029] After the lithium ferrite particles deposited the carbon film in the device for 30 minutes, the energy source was turned off, the vacuum was turned off, the power was turned off, and the device was cooled to room temperature to obtain a carbon-coated lithium ferrite material (LFO-C-1) with a coating layer of about 100 nm.

[0030] Part of the LFO-C-1 material was taken out and exposed to air with a humidity of 20% for 24 hours to obtain the exposed material LFO-C-1-24h for use.

[0031] Example 2

[0032] This embodiment provides a method for preparing carbon-coated lithium ferrite by physical vapor deposition, and the specific steps are as follows:

[0033] Placing lithium ferrite LFO particles in a physical vapor deposition coating device, and allowing the lithium ferrite to circulate in the powder coating device;

[0034] The lithium titanate particles circulating in the device were coated by physical vapor deposition. The vacuum system was turned on and the vacuum was pumped to 9×10-3 Pa, preheat for 60 min, introduce argon and maintain the equipment pressure at 0.4 Pa, set the temperature to 300 ° C, the current to 3 A, the voltage to 400 V, and start depositing the carbon film;

[0035] After the lithium ferrite particles deposited the carbon film in the device for 60 minutes, the energy source was turned off, the vacuum was turned off, the power was turned off, and the device was cooled to room temperature to obtain a carbon-coated lithium ferrite material (LFO-C-2) with a coating layer of about 300 nm.

[0036] Part of the LFO-C-2 material was taken out and exposed to air with a humidity of 20% for 24 hours to obtain the exposed material LFO-C-2-24h for use.

[0037] Example 3

[0038] This embodiment provides a method for preparing carbon-coated lithium ferrite by physical vapor deposition, and the specific steps are as follows:

[0039] Placing lithium ferrite LFO particles in a physical vapor deposition coating device, and allowing the lithium ferrite to circulate in the powder coating device;

[0040] The lithium titanate particles circulating in the device were coated by physical vapor deposition. The vacuum system was turned on and the vacuum was pumped to 9×10 -3 Pa, preheat for 60 min, introduce argon and maintain the equipment pressure at 0.4 Pa, set the temperature to 400 ° C, the current to 3 A, the voltage to 400 V, and start depositing the carbon film;

[0041] After the lithium ferrite particles were deposited with a carbon film in the device for 120 minutes, the energy source was turned off, the vacuum was turned off, the power was turned off, and the device was cooled to room temperature to obtain a carbon-coated lithium ferrite material (LFO-C-3) with a coating layer of about 700 nm.

[0042] Part of the LFO-C-3 material was taken out and exposed to air with a humidity of 20% for 24 hours to obtain the exposed material LFO-C-3-24h for use.

[0043] Comparative Example 1

[0044] Comparative Example 1 provides an uncoated lithium-rich lithium iron oxide material LFO.

[0045] A portion of the LFO material was taken out and exposed to air with a humidity of 20% for 24 hours to obtain the exposed material LFO-24h for use.

[0046] Comparative Example 2

[0047] Comparative Example 2 provides a method for preparing carbon-coated lithium-rich lithium iron oxide, and the specific steps are as follows:

[0048] Glucose was used as the carbon source and a tubular furnace was used for the coating experiment. The glucose and the lithium iron-rich material were evenly mixed and placed in a tubular furnace for high-temperature carbonization at 400°C for 6 hours to obtain a carbon-coated lithium iron-rich material (denoted as LFO-P / C).

[0049] A portion of the C@LFO material was taken out and exposed to air with a humidity of 20% for 24 hours to obtain the exposed material LFO-P / C-24h for use.

[0050] Comparative Example 3

[0051] Comparative Example 3 provides a method for preparing carbon-coated lithium ferrite by physical vapor deposition, and the specific steps are as follows:

[0052] Placing lithium ferrite LFO particles in a physical vapor deposition coating device, and allowing the lithium ferrite to circulate in the powder coating device;

[0053] The lithium titanate particles circulating in the device were coated by physical vapor deposition. The vacuum system was turned on and the vacuum was pumped to 9×10 -3 Pa, preheat for 60 min, introduce argon and maintain the equipment pressure at 0.4 Pa, set the temperature to 400 ° C, the current to 3 A, the voltage to 400 V, and start depositing the carbon film;

[0054] After the lithium ferrite particles deposited the carbon film in the device for 300 minutes, the energy source was turned off, the vacuum was turned off, the power was turned off, and the device was cooled to room temperature to obtain a carbon-coated lithium ferrite material (LFO-C-4) with a coating layer of about 3 μm.

[0055] Performance Testing

[0056] The materials provided in the above embodiments and comparative examples are used as positive electrode active materials of lithium ion batteries, and the batteries are assembled as follows:

[0057] Preparation of positive electrode sheets: Conductive agent Super-P, adhesive PVDF, and positive electrode active material are dispersed in solvent N-methylpyrrolidone in a mass ratio of 10:10:80, mixed evenly to form positive electrode slurry, and then the positive electrode slurry is evenly coated on the current collector aluminum foil. After drying, rolling, die-cutting, and drying, the lithium-supplemented positive electrode sheet is obtained.

[0058] The negative electrode directly uses lithium sheets.

[0059] Assemble button batteries using the lithium-supplemented positive electrode sheet, negative electrode sheet, separator, gasket and shrapnel, and leave them to stand for 24 hours before use.

[0060] After the battery is assembled, its initial charge and discharge specific capacity is tested as follows: the above battery is charged to 4.5V at 0.1C constant current, and then discharged to 2.5V at 0.1C constant current, and the initial charge and discharge efficiency of the battery is observed.

[0061] The battery performance test results of the embodiments and comparative examples are shown in Table 1.

[0062] Table 1 Battery performance test results

[0063]

[0064]

[0065] Examples 1-3 all use the physical vapor deposition coating method of the present invention to modify the lithium-rich lithium ferrite. By comparing the battery results with the uncoated lithium-rich lithium ferrite material in Comparative Example 1 and the carbon-coated lithium-rich lithium ferrite material in Comparative Example 2, the materials in Examples 1-3 can maintain a charging capacity of more than 650 mAh / g after being exposed to 20% air humidity for 24 hours, while the material in Comparative Example 1 has a charging capacity of only 181.54 mAh / g after being exposed to 20% humidity for 24 hours, and the material in Comparative Example 2 has a charging capacity of only 442.96 mAh / g after being exposed to 20% air humidity for 24 hours. It can be seen that after the lithium-rich lithium ferrite is modified by the coating method of the present invention, the surface of the material is evenly and densely covered with a layer of coating, so that the material can fully isolate water and carbon dioxide in the air, thereby ensuring the purity of the lithium ferrite and the lithium replenishment effect, while improving the electrical conductivity of the material. By comparing the battery results of Examples 1-3 with those of Comparative Example 3, it can be seen that a coating layer that is too thick will lead to a decrease in material capacity, further resulting in a poor lithium replenishment effect.

Claims

1. A carbon coating method for lithium iron-rich lithium, characterized in that: The following steps are involved: A physical vapor deposition method is used to perform carbon film deposition on circulating lithium ferrite particles placed in a physical vapor deposition coating device; After the deposition is completed, the device power is turned off and cooled to room temperature to obtain a carbon-coated lithium ferrite material.

2. The carbon coating method according to claim 1, characterized in that: The circulation flow rate of the lithium ferrite particles in the coating device is 0.1-100g / s. After the circulation flow is stabilized, argon gas is introduced into the coating device.

3. The carbon coating method according to claim 1, characterized in that: The physical vapor deposition method is a magnetron sputtering method, the carbon source used is a graphite target with a purity of 99.99%, and the particle size D50 of the lithium ferrite particles is 2-30 μm.

4. The carbon coating method according to any one of claims 1 to 3, characterized in that: The carbon film deposition process is as follows: Turn on the vacuum system and wait until the vacuum reaches 2×10 -3 Pa to 9×10 -3 Pa, preheat for 60 minutes, introduce argon and maintain the equipment pressure at 0.1-2Pa, set the temperature to 30-400℃, the current to 2-4A, the voltage to 300-400V, and start carbon film deposition.

5. The carbon coating method according to claim 4, characterized in that: The temperature of carbon film deposition is 100-400°C and the time is 1-180 min.

6. The carbon coating method according to claim 4, characterized in that: The thickness of the coating layer of the obtained carbon-coated lithium ferrite material is 30-900 nm.

7. The carbon coating method according to any one of claims 1 to 6, characterized in that: After the obtained carbon-coated lithium ferrite material was exposed to air humidity of 20% for 24 hours, its charge specific capacity was still maintained above 650 mAh / g.

8. Carbon-coated lithium ferrite material, characterized in that: The carbon coating method is used to prepare the carbon coating.

9. A lithium-ion battery, characterized in that It is prepared using the carbon-coated lithium ferrite material described in claim 8.

10. The lithium ion battery according to claim 9, characterized in that: The lithium-ion battery comprises a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode is a lithium sheet, the positive electrode comprises a current collector and an electrode active layer combined with the surface of the current collector, and the positive electrode active material in the electrode active layer is a carbon-coated lithium iron-rich lithium material.

Citation Information

Cited By

  • Carbon-coated lithium ferrite material

    CN119965249A